Immediate Autogenous Extracted Tooth as a Grafting Material For Fresh Socket Preservation: a Systematic Review - Zurab Khabadze; Oleg Mordanov; Marina Dashtieva; Ia Todua; Julia Generalova; Artemy Nedashkovsky; Meri Sheroziia; Saida Adbulkerimova; Yusup Bakaev (Universidad de Concepción., 2021)
Objectives: To evaluate the use of extracted autogenous teeth for socket preservation after tooth extraction. Material and Methods: Cochrane, Scopus, and PubMed databases search was conducted to identify human clinical studies reporting the clinical, radiographic and/or histological outcomes of socket preservation techniques with autogenous extracted tooth Only studies published in English language in the last 10 years were included in the study. Results: In total, 82 articles were identified. Five articles were included in the review. They included 58 teeth that were prepared as a graft for socket preservation. The grafts derived from autogenous teeth were presented in three forms: particles, blocks and powder. The mean bone loss ranged from 0.28 mm to 0.41mm in height and 0.15 mm in width.Conclusion: Immediate autogenous extracted tooth as a grafting material for fresh socket preservation is promising for future daily clinical practice. More clinical comparative studies are needed